MD1003 (high-dose biotin) for the treatment of progressive multiple sclerosis: A randomised, double-blind, placebo-controlled study - Tourbah, Ayman; Lebrun-Frenay, Christine; Edan, Gilles; Clanet, Michel; Papeix, Caroline; Vukusic, Sandra; De Sèze, Jerome; Debouverie, Marc; Gout, Olivier; Clavelou, Pierre; Defer, Gilles; Laplaud, David-Axel; et al. (Multiple sclerosis, 2016)
Treatment with MD1003 (high-dose biotin) showed promising results in progressive multiple sclerosis (MS) in a pilot open-label study. To confirm the efficacy and safety of MD1003 in progressive MS in a double-blind, placebo-controlled study. Patients (n = 154) with a baseline Expanded Disability Status Scale (EDSS) score of 4.5-7 and evidence of disease worsening within the previous 2 years were randomised to 12-month MD1003 (100 mg biotin) or placebo thrice daily, followed by 12-month MD1003 for all patients. The primary endpoint was the proportion of patients with disability reversal at month 9, confirmed at month 12, defined as an EDSS decrease of ⩾1 point (⩾0.5 for EDSS 6-7) or a ⩾20% decrease in timed 25-foot walk time compared with the best baseline among screening or randomisation visits. A total of 13 (12.6%) MD1003-treated patients achieved the primary endpoint versus none of the placebo-treated patients (p = 0.005). MD1003 treatment also reduced EDSS progression and improved clinical impression of change compared with placebo. Efficacy was maintained over follow-up, and the safety profile of MD1003 was similar to that of placebo. MD1003 achieves sustained reversal of MS-related disability in a subset of patients with progressive MS and is well tolerated.